(untitled) (TAJ: Journal of Teachers Association, 2009)
Objectives: To see the (a) type of congenital heart disease, (b) Clinical presentation of the cases, (c) association with extra-cardiac anomalies and disease, (d) complications of different CHD, (e) outcome of patients during hospital stay. Methodology: it was a prospective study conducted in the department of pediatrics of Rajshahi Medical College & Hospital over a period of one year.115 children from birth to 12 years of age who had congenital heart disease confirmed by echocardiography were included. All patients were treated conservatively and observed for immediate out come during the hospital stay. Result: major types of CHD were VSD (42.6%), TOF (18.3%), ASD (14.8%), PDA (7.8%). Male outnumbers female child. Common symptoms were breathlessness (60%), fatigue (54.8%), cough (43.5%), poor weight gain (41.7%), recurrent chest infection (34.8%), fever (28.7%), feeding problems (26.1%), palpitation (21.7%) and bluish discoloration of lips and fingertips (20%). Murmur with or without thrill and cardiomegaly was the most important cardiac finding. Frequently observed complications were heart failure, pulmonary hypertension and growth failure. doi: 10.3329/taj.v21i1.3221 TAJ 2008; 21(1): 58-62